Four Ways to Another Religion’s Ultimate - Hustwitt, J. R. (Open theology, 2018)
The prospect of recognizing the ultimate is a matter of interpretation. As such, hermeneutics is used as a framework for describing the interactions of self, language, and the other (whether culturally other or ultimately other). Questioning whether religious ultimacy can be recognized across religious boundaries is based on a mistaken assumption that differences between religions are qualitatively different than differences within a religion. Hermeneutically speaking, intra-communal difference and inter-communal difference are of the same kind. If humans can negotiate the former, they can negotiate the latter. Recognizing ultimacy is an intersubjective act of phronēsis, or practical wisdom. As such, it cannot be explained in any detail apart from the concrete particulars of each encounter. Below is an account of recognizing the Ultimate, analyzed into four explanatory ways: its immediate quality (uncanniness), its vehicle (the classic), its cultural-linguistic mechanism (metaphorical appropriation), and its ontological implications (a signifying cosmos). Each way offers a different type of explanation as to how a person can recognize another religion’s ultimate. I begin with the most concrete: spontaneous feeling, and work my way to more speculative implications.